A Multi‐Center Prospective Study on the Healing of Neuro‐Ischemic Ulcers in Singapore: A Prospective Cohort Study - Lingyan Meng; Priya Bishnoi; Zhiwen Joseph Lo; Enming Yong; Tze Tec Chong; David Carmody; Rajesh Babu Dharmaraj; Yi Zhen Ng; Keith Harding; Pei Ho (Health Science Reports)
ABSTRACT Background and Aims Neuro‐ischemic ulcers (NIU) present a substantial clinical and economic burden on the healthcare systems. This study aims to evaluate their healing rate, associated healthcare resource utilization, and prognostic factors influencing healing. Methods Consecutive patients attended specialist clinics or admitted to wards in three tertiary hospitals for new or existing NIUs from November 2019 to November 2021 were eligible for this study. Each participant was followed up three times (1‐month, 3‐month and 6‐month after enrollment), with ulcer healing as the primary outcome of interest. Cox regression analysis was performed to identify independent predictors of NIU healing. Results In total, 439 patients were recruited. Six months after they seek care in the tertiary healthcare setting, 36.0% of the participants had their ulcer fully healed. Male gender (adjusted HR: 0.71, 95% CI: 0.53–0.93), history of coronary intervention (adjusted HR: 0.62; 95% CI: 0.41–0.93), requirement of lower extremity revascularization (adjusted HR: 0.72; 95% CI: 0.54–0.98) and offloading (adjusted HR: 0.61; 95% CI: 0.46–0.81) were found to be associated with failure to heal. Ulcers located over the toes (adjusted HR: 1.64; 95% CI: 1.17–2.32) was associated with better healing. Dependent activity of daily living (adjusted HR: 0.74; 95% CI: 0.55–1.01) was also potentially a risk factor for slow healing with borderline significance. Nonhealed group of patients incurred higher requirement of revascularization (42.3% vs. 25.3%, p < 0.001), negative pressure wound therapy (40.6% vs. 29.7%, p = 0.03), off‐loading (57.3% vs. 46.8%, p = 0.04) and antibiotic treatment (45.2% vs. 26.6%, p < 0.001), compared to those in the healed group. Conclusion NIU imposes a significant burden on both patients and the healthcare system in Singapore, with low healing rates even after 6 months of tertiary‐level care. Early identification and risk stratification of high‐risk patients may help improve outcomes.